2020
DOI: 10.1111/hae.14153
|View full text |Cite
|
Sign up to set email alerts
|

Detection and evaluation of haemophilic arthropathy: Which tools may be considered more reliable

Abstract: Introduction Progressive arthropathy is the main cause of morbidity in patients with severe haemophilia. Diagnostic imaging can detect even subclinical arthropathy and impact prophylactic treatment. However, in most clinical settings the regular joint evaluation and follow‐up are based on clinical evaluation and patient's personal reporting of problems, while diagnostic imaging is not regularly employed. Aim The aim of our prospective study was to assess how ultrasound (US), clinical examination, patient's sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 31 publications
2
32
0
Order By: Relevance
“…31 Plut et al found that the negative predictive value of physical examination was 40% for joint damage compared with MRI. 19 These high published percentages of subclinical synovitis could be related to the fact that synovitis does not usually show joint tension, nor is it painful. 3,32 It appears that synovial hypertrophy is more frequently subclinical in the elbows than in the knees and ankles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 Plut et al found that the negative predictive value of physical examination was 40% for joint damage compared with MRI. 19 These high published percentages of subclinical synovitis could be related to the fact that synovitis does not usually show joint tension, nor is it painful. 3,32 It appears that synovial hypertrophy is more frequently subclinical in the elbows than in the knees and ankles.…”
Section: Discussionmentioning
confidence: 99%
“…De la Corte‐Rodriguez et al demonstrated that 18/167 (10.7%) patients with no history of haemarthrosis and with HJHS 0 had subclinical synovitis in HEAD‐US 31 . Plut et al found that the negative predictive value of physical examination was 40% for joint damage compared with MRI 19 . These high published percentages of subclinical synovitis could be related to the fact that synovitis does not usually show joint tension, nor is it painful 3,32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…endothelial specific isoform of type XVIII collagen (COL-18N), tissue inhibitor of metalloproteinase (TIMP-1), degraded type II collagen (C2M) and inflammatory markers, e.g. VEGF, interleukin-6 (IL-6), neutrophil extracellular traps (NETs) showed statistically significant correlations with the degree of HA, while bone markers did not show this correlation [7][8][9][10][11][12][13][14][15]. Kjeld et al previously showed that the cartilage marker COL-18N was significantly associated with the annual bleeding rate (ABR), a parameter directly associated with the degree of HA on X-rays [16].…”
Section: Burden Of Diseasementioning
confidence: 99%
“…
With great interest, we read the original article 'Detection and evaluation of haemophilic arthropathy: Which tools may be considered more reliable' by Plut et al 1
…”
mentioning
confidence: 99%